The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0153987
|View full text |Cite
|
Sign up to set email alerts
|

Recent Warming, Rather than Industrial Emissions of Bioavailable Nutrients, Is the Dominant Driver of Lake Primary Production Shifts across the Athabasca Oil Sands Region

Abstract: Freshwaters in the Athabasca Oil Sands Region (AOSR) are vulnerable to the atmospheric emissions and land disturbances caused by the local oil sands industry; however, they are also affected by climate change. Recent observations of increases in aquatic primary production near the main development area have prompted questions about the principal drivers of these limnological changes. Is the enhanced primary production due to deposition of nutrients (nitrogen and phosphorus) from local industry or from recent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 40 publications
(76 reference statements)
3
34
2
Order By: Relevance
“…Studies have also reported an association between natural gradients, such as flooding or regional warming, and bitumen-associated contaminants in lakes (e.g., Hall et al 2012;Summers et al 2016). In the present study, 51% of the variation in 17 heavy metals or priority pollutants could be attributed to differences between reference and post-development phases of mining activity.…”
Section: Discussionsupporting
confidence: 51%
“…Studies have also reported an association between natural gradients, such as flooding or regional warming, and bitumen-associated contaminants in lakes (e.g., Hall et al 2012;Summers et al 2016). In the present study, 51% of the variation in 17 heavy metals or priority pollutants could be attributed to differences between reference and post-development phases of mining activity.…”
Section: Discussionsupporting
confidence: 51%
“…Total N deposition in the oil sands region estimated for current development is 165 eq/ha per year (Cho et al 2017) and may be associated with increased productivity in local waterbodies (Hazewinkel et al 2008). Summers et al (2016) suggested, however, that warming, rather than nutrient enrichment, is driving increased productivity in local lakes, which may have a role in explaining some of our results. Inconsistencies in the deposition of nitrogenous compounds on the landscape and transportation to watercourses over time may also explain some noise in TN among stations compared with TP.…”
Section: Discussionmentioning
confidence: 67%
“…Further, as climate change proceeds, anticipated changes in permafrost thaw, length of seasonal ice cover, and water temperatures will likely increase the productivity of northern ecosystems (Antoniades et al 2011). In fact, increases in internal P loading in boreal lakes in northern Alberta due to climate change have resulted in long-term increases in lake productivity (Hazewinkel et al 2008;Kurek et al 2013;Summers et al 2016).…”
Section: Understudied Ecosystemsmentioning
confidence: 99%